PROPUESTA DE UN PLAN DE MARKETING TURÍSTICO PARA LA GASTRONOMÍA DEL CANTÓN SARAGURO, PROVINCIA DE LOJA - PIZARRO MOROCHO, MARCIA ENIDT (2016)
Tourism, undoubtedly, is a fundamental axis for economic recovery, job creation, local and foreign investment, the development of hotel infrastructure, roads, ports and above all, an attractive currency for countries of the world. Ecuador has a variety of landscapes, fauna, flora, ethnic groups, food and perform various forms of tourism, be it adventure, cultural, business, rural, community, gastronomy, etc. In the Southern Region of the country is the city of Loja, characterized by its friendly people, has 16 cantons which have great tourism potential, among them are the Saraguro canton city with many natural, cultural attractions and a variety gastronomy, full of traditions and customs that the people of Saraguro still keeps, that is why it is important to enhance the promotion and dissemination of the cuisine of Canton Saraguro, contributing to tourism development, for which it has raised overall objective "Develop a marketing plan to promote food, contributing to tourism and economic development of the Canton Saraguro, Loja Province". And three specific objectives: a diagnosis of the current situation of the cuisine of Canton Saraguro, Loja Province, Offer Marketing Plan for the cuisine of Canton Saraguro in order to position it as one of the main attractions of the southern region Socialize country and the marketing plan with the Canton Saraguro. To comply with the first objective "will make a diagnosis of the current situation of the cuisine of Canton Saraguro, Loja Province" deductive, descriptive and historical method which allowed accurate collection of reliable information was used, obtaining specific findings Canton Saraguro gastronomy; within the techniques used are; direct observation, surveys, interviews, FODA analysis, together with attractive inventory records of the Ministry of Tourism. As for the second objective: "To propose a marketing plan for the cuisine of Canton Saraguro in order to position it as one of the main attractions of the southern region," they were taken as a basis the results of the diagnosis made in the first objective, which allowed us to meet more widely as is managing the development and dissemination of promoting the cuisine of Saraguro. To fulfill the third objective: "Socialize the marketing plan with the Canton Saraguro". It was executed based on 3 stages: First: Initial (on), through calls, agenda and presentations, they were also used to inform the authorities and population of the Canton Saraguro on the day and date of socialization. 5 Second: Design, development, presenting the topic was conducted with the support of audiovisual material. Third, results, conclusions and recommendations presented by the attendees were obtained. We conclude that there is adequate training to members of companies dedicated to gastronomy in terms of care and customer service, existing uncoordinated by different owners of the restaurants in Saraguro as to work together in the Canton Saraguro for the proper promotion and dissemination of gastronomy and design a marketing plan allows you to spread gastronomy Saraguro at local, national and international level, tools must be in line with current market trends, allowing the development of tourism canton study. The necessary recommendations were made based on the result of the implementation of the project such as: the Municipality of the Canton Saraguro must improve and strengthen the training to persons working with the hospitality industry aimed to solve problems and provide proper customer facing a large number of tourists, the owners of the different restaurants is recommended strategic alliances, work together to provide good customer service, disseminate and promote food, to attract more tourists both domestic and foreign to Canton Saraguro and finally to implement the Marketing Plan with all the tools and strategies proposed for this activity is optimized and to be gastronomy as a tourist product of the town.